DNA barcodes discriminate freshwater fishes from the Paraiba do Sul River Basin, São Paulo, Brazil - Pereira, Luiz H. G. [UNESP]; Maia, Glaucia M. G.; Hanner, Robert; Foresti, Fausto; Oliveira, Claudio (Informa Healthcare, 2011)
Background and aims: Considering the promising use of DNA barcoding for species identification, the importance of the freshwater fish fauna of the Paraiba do Sul River Basin, and its advanced stage of degradation, the present study evaluated the effectiveness of DNA barcoding to identify the fish species in this basin.Materials and methods: A total of 295 specimens representing 58 species belonging to 40 genera, 17 families, and 5 orders were sequenced.Results: The DNA barcodes discriminated all species analyzed without ambiguity. The results showed a pronounced difference between conspecific and congeneric pair-wise sequence comparisons, demonstrating the existence of a "barcode gap" for the species analyzed. The nearest-neighbor distance analysis showed only three cases with Kimura two-parameter values lower than a 2% divergence threshold. However, the patterns of divergence observed in each case remained sufficient to discriminate each species, revealing the accuracy of DNA barcoding even cases with relatively low genetic divergence. At the other extreme, three species displayed high genetic sequence divergence among conspecifics. For two cases, Characidium alipioi and Geophagus proximus, barcoding proved effective at flagging possible new species. For another case, Astyanax bimaculatus, the use of DNA barcoding of the comparison of shared freshwater fish fauna between different basins revealed itself as highly useful in disclosing that the previously identified A. bimaculatus "cluster A" probably represents the species Astyanax altiparanae.Conclusion: The present study is among the first to assess the efficiency of barcoding for the Brazilian freshwater fishes. The results demonstrate the utility of barcoding to identify the fauna from this basin, contribute to an enhanced understanding of the differentiation among species, and to help flag the presence of overlooked species.
Keywords: Species identification; hidden diversity; biodiversity; Neotropical region; freshwater fishes; FISH-BOL